Semaphorin 3F and Netrin-1: The Novel Function as a Regulator of Tumor Microenvironment - Nakayama, Hironao; Kusumoto, Chiaki; Nakahara, Masako; Fujiwara, Akira; Higashiyama, Shigeki (Frontiers in Physiology, 2018)
Axon guidance molecules play important roles to regulate proper neuronal networking during neuronal development. They also have non-neuronal properties, which include angiogenesis, inflammation, and tumor development. Semaphorin 3F (SEMA3F), a member of the class 3 semaphorins, was initially identified as an axon guidance factor that repels axons and collapses growth cones. However, SEMA3F has similar effects on endothelial cells (ECs) and tumor cells. In this review, we discuss the novel molecular mechanisms underlying SEMA3F activity in vascular and tumor biology. Recent evidence suggests that SEMA3F functions as a PI3K-Akt-mTOR inhibitor in mammalian cells, including T cells, ECs, and tumor cells. Therefore, SEMA3F may have broad therapeutic implications. We also discuss the key role of axon guidance molecules as regulators of the tumor microenvironment. Netrin-1, a chemoattractant factor in the neuronal system, promotes tumor progression by enhancing angiogenesis and metastasis. Moreover, our recent studies demonstrate that netrin-1/neogenin interactions augment CD4+ T cell chemokinesis and elicit proinflammatory responses, suggesting that netrin-1 plays a key role in modulating function of tumor and its surrounding cells in the tumor microenvironment. Overall, this review focuses on SEMA3F and netrin-1 signaling mechanisms to understand the diverse biological functions of axon guidance molecules.